iLearning education based on gamification blockchain - Qurotul Aini; Nur Azizah; Rahmat Salam; Nuke Puji Lestari Santoso; Shofiyul Millah (Institute of Advanced Engineering and Science, 2022)
learning process implemented in universities due to COVID-19 has brought significant disruption to education. Interest and motivation to learn are very important in the learning process. It takes a platform that supports students to be motivated in running the activity hours well. Learning techniques that can be chosen are collaborative and creative learning in achieving effective graduate outcomes with the support of the Merdeka Campus program. This research aims to make gamification techniques to make students more creative, innovative, and interactive by utilizing the concepts of learning and playing. Furthermore, a learning platform based on blockchain technology can support quality universities as a layer of control in implementing security and fun learning. With gamification techniques in collaboration with blockchain technology, all devices connected to the network will become nodes or servers. This study uses agile development methods based on iterative and incremental models to create a distributed storage blockchain algorithm, and IPFS used to build the GamiChain iLearning education model (gamification blockchain). It can be concluded that GamiChain (gamification blockchain) can support the Merdeka Campus program, which can provide facilities for students to develop their potential and prepare excellent and outstanding graduates.